2019
DOI: 10.1002/cche.10164
|View full text |Cite
|
Sign up to set email alerts
|

Moisture effects on robustness of sorghum grain protein near‐infrared spectroscopy calibration

Abstract: Background and objectives A near‐infrared (NIR) spectroscopy method was developed for rapid and nondestructive evaluation of protein content of intact sorghum grains. Effect of grain sample moisture variation on the robustness of protein calibration was investigated. Findings An initial NIR protein calibration model with sorghum grains in 7.28%–11.57% moisture content range with coefficient of determination (R2) of 0.94 and standard error of cross‐validation (SECV) of 0.41%, predicted protein content of an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Peiris et al (2019) showed that moisture content of sorghum grains affected the performance of the NIR protein calibration model and inclusion of moisture variation in the calibration sample set improved the robustness of the model. Therefore, the C1 samples intended for the development of a robust NIR calibration for protein content determination in sound sorghum grain samples had a moisture range from 7.28% to 18.68% (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Peiris et al (2019) showed that moisture content of sorghum grains affected the performance of the NIR protein calibration model and inclusion of moisture variation in the calibration sample set improved the robustness of the model. Therefore, the C1 samples intended for the development of a robust NIR calibration for protein content determination in sound sorghum grain samples had a moisture range from 7.28% to 18.68% (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This may hold true when developing NIR calibrations for other sorghum traits as well and thus warrants further research in developing calibrations for assessing other traits of weathered sorghum. The most important NIR bands carrying the information on sorghum protein is found in the 950–1200 nm region of the spectra (Peiris et al., 2019). Since weathered grains show spectral distortions in this spectral region, correction of such distortions in spectra by EMSC preprocessing improved the prediction accuracy of the NIR protein calibration when applied to weathered grains allowing for NIRS to be used on sample sets containing weathered sorghum grain samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crude protein content and specific amino acids have been analyzed by NIR (Peiris et al, 2019). The crude protein content is comparatively higher in sorghum than wheat, corn, and barley, and morphologically, sorghum grains are not covered by a protective layer.…”
Section: Nir Analysismentioning
confidence: 99%